Association between lipid trajectories during pregnancy and risk of postpartum glucose intolerance after gestational diabetes mellitus: a cohort study - Yang, Zhuofan; Li, Zhuyu; Cheng, Yunjiu; Chen, Peisong; Wang, Dongyu; Chen, Haitian; Chen, Wei; Wang, Zilian (Acta diabetologica, 2022)
Aims To assess lipid trajectories throughout pregnancy in relation to early postpartum glucose intolerance in women with gestational diabetes mellitus (GDM). Methods This prospective cohort study included 221 Chinese women with GDM who completed plasma lipid test in each trimester of pregnancy and oral glucose tolerance test at 6–9 weeks postdelivery between January 1, 2018 and January 8, 2020. Using the group-based trajectory modeling, total cholesterol (TC), triglyceride (TG), low-density lipoprotein-cholesterol (LDL-c), and high-density lipoprotein-cholesterol(HDL-c) were identified separately as three trajectories: low, moderate, and high trajectory. The associations between lipid trajectories and early postpartum glucose intolerance were all evaluated. Results Seventy-three participants developed postpartum glucose intolerance. For patients in low, moderate and high trajectory, the incidence of postpartum glucose intolerance was 38.4%, 34.9%, and 17.9%, respectively. GDM women with lower LDL-c trajectories presented a higher risk of postpartum glucose intolerance. The adjusted odds ratio (95% CI) for glucose intolerance was 3.14 (1.17–8.39) in low LDL-c trajectory and 2.68 (1.05–6.85) in moderate trajectory when compared with the high one. However, TC trajectory was not associated with the risk of postpartum glucose intolerance, nor were TG trajectory and HDL-c trajectory. Moreover, a significant difference of insulin sensitivity was observed in participants with different LDL-c trajectories; participants in high LDL-c trajectory had the highest insulin sensitivity, whereas the women in low LDL-c trajectory had the lowest insulin sensitivity ( P = 0.02). Conclusions The high trajectory of LDL-c during pregnancy may play a protective role on postpartum glucose intolerance in women with GDM. Further studies are warranted to explore the underlying mechanism. Trial registration The study was reviewed and approved by the Institutional Review Board of The First Affiliated Hospital of Sun Yat-sen University (reference number: [2014]No. 93). All participants provided written informed consent forms, and the ethics committee approved this consent procedure.